Presence and Plant Uptake of Heavy Metals in Tidal Marsh Wetland Soils - Chintapenta, Lathadevi K.; Ommanney, Katharine I.; Ozbay, Gulnihal (Frontiers in Public Health, 2022)
Marsh grasses have been used as efficient tools for phytoremediation and are known to play key roles in maintaining ecosystem functions by reducing the contamination of coastlines. This study was initiated to understand how human activities in wetlands can impact ion-heavy metal concentrations in relation to native and invasive marsh grasses. The study site, Blackbird Creek (BBC) is a tidal wetland that experiences agricultural, fishing, recreational, residential and other anthropogenic activities throughout the year. Heavy metals cadmium, arsenic, and lead in the soils and marsh grasses were monitored along with the ion compositions of soils. The main objective of this study was to understand if the marsh soils containing monotypic stands of native (Spartina) and non-native (Phragmites) vegetation display similar levels of heavy metals. Differences were observed in the concentrations of heavy metals at study sites with varying marsh vegetation types, and in soils containing vegetation and no vegetation. The soils with dense Spartina and Phragmites stands were anaerobic whereas soil at the boat ramp site was comparatively less anaerobic and also had increased levels of cadmium. Heavy metal concentrations in soil and Phragmites leaves were inversely correlated whereas they were positively correlated in Spartina sites. Electrical conductivity and pH levels in soil also showed increased cadmium and arsenic concentrations. These findings collectively infer that human activities and seasonal changes can increase soil complexities affecting the bioavailability of metals.